Unveiling the Features of Mercury-Associated Minimal Change Disease: Comparison with Primary Minimal Change Disease - Ai-bo Qin; Xiao-juan Yu; Su-xia Wang; Fu-de Zhou; Ming-hui Zhao (Karger Publishers, 2020)
Introduction: Long-term exposure to mercury can cause minimal change disease. However, the current understanding of mercury-associated minimal change disease (M-MCD) is inadequate. To improve the understanding of M-MCD, this study retrospectively analyzed the clinicopathological, ultrastructural, and prognostic features of M-MCD, in comparison with primary minimal change disease (P-MCD). Methods: We retrospectively analyzed the clinicopathological data of 21 M-MCD patients and 21 P-MCD patients. Electron micrographs of glomerular capillaries were taken, and the foot process width (FPW) was measured. A receiver operating characteristics (ROC) curve analysis was performed to determine the optimum cutoff value of FPW that can differentiate the M-MCD from P-MCD. Results: M-MCD patients presented similar clinical and routine pathological characteristics with P-MCD patients but had lower levels of FPW (935.0 [interquartile range (IQR) 853.7-1,176.7] nm vs. 1,403.2 [IQR 1,089.2-1,841.8] nm, p = 0.002). ROC curve analysis showed that FPW value below 1,385 nm might help to differentiate M-MCD from P-MCD (area under the curve of 0.787, sensitivity of 94.7%, and specificity of 52.4%). For patients with M-MCD, 77.8% achieved complete remission after mercury detoxification monotherapy. Patients with M-MCD had a lower relapse rate than patients with P-MCD (0 vs. 47.1%, p = 0.003). In addition, there was no significant difference in remission time between M-MCD patients treated with mercury detoxification monotherapy and those initially treated with immunosuppressive therapy (2.0 [IQR 1.0-6.0] months vs. 2.0 [IQR 1.5-2.5] months, p = 0.606). Conclusions: M-MCD patients showed similar clinicopathological features with P-MCD patients, but with less severe foot process effacement, suggesting different pathogenesis of these 2 disease entities. The treatment of mercury detoxification was highly effective for patients with M-MCD and can be considered as a primary choice in clinical practice.